The contribution of ICT adoption to sustainability: households' perspective. Issue 3 (3rd June 2019) - Ziemba, Ewa
Abstract : Purpose: The purpose of this paper is to advance the information society research by examining and better understanding the impact of the adoption information and communication technologies (ICT) within households on improving sustainability. Design/methodology/approach: The survey questionnaire was used and data collected from 679 Polish households were statistically analyzed to understand the phenomena of ICT adoption and sustainability as well as identify correlations between them. Findings: The research findings reveal that the ICT adoption is well described by the ICT outlay, information culture, ICT management and ICT quality, whereas sustainability is composed of ecological, economic, socio-cultural and political sustainability. Furthermore, the ICT quality, ICT management and information culture have a significant impact on sustainability, whereas the ICT outlay does not have such an impact. Research limitations/implications: The research sample included Polish households only. Researchers may use the proposed approach and methodology to do similar analyses with different sample groups in other countries. Practical implications: Households may find the results appealing and useful in enhancing the adoption of ICT, experiencing the full potential of ICT and deriving various benefits from the ICT adoption. The findings can help governments develop sound ICT adoption plans for implementing the 2030 Agenda for Sustainable Development. Originality/value: The paper provides and verifies a new theoretical model of sustainable information society to depict various dimensions shaping the ICT adoption and their impact on different types of sustainability in the context of households.